2018
DOI: 10.1371/journal.pone.0206891
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral delayed endolymphatic hydrops evaluated by bilateral intratympanic injection of gadodiamide with 3T-MRI

Abstract: The purpose of this study was to assess the diagnostic performance of 3T MRI after intratympanic injection of gadodiamide for delayed endolymphatic hydrops (DEH), and assess the relationship between endolymphatic hydrops (ELH) and vestibular function in patients diagnosed with DEH and confirmed by 3T MRI. Nineteen patients clinically diagnosed with DEH (11 ipsilateral DEH, 8 contralateral DEH) participated in this study. Diluted gadodiamide was administered to the bilateral tympanic cavity by injection through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Our result was in agreement with that reported by Schuknecht et al who found that 80% of the ipsilateral DEH patients had unilateral caloric weakness in the hydropic ear and 9% had such hypofunction in the opposite ear (29). The substantially higher incidence of abnormal CP in the ear with precedent hearing loss than in the contralateral ear might be ascribed to the fact that: (1) bilateral ELH is commonly present in ipsilateral DEH patients, as demonstrated by gadolinium-enhanced MRI (30,31), and (2) the area of ELH in the deaf ear was significantly larger than or practically equivalent to that of the better-hearing ear (31).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our result was in agreement with that reported by Schuknecht et al who found that 80% of the ipsilateral DEH patients had unilateral caloric weakness in the hydropic ear and 9% had such hypofunction in the opposite ear (29). The substantially higher incidence of abnormal CP in the ear with precedent hearing loss than in the contralateral ear might be ascribed to the fact that: (1) bilateral ELH is commonly present in ipsilateral DEH patients, as demonstrated by gadolinium-enhanced MRI (30,31), and (2) the area of ELH in the deaf ear was significantly larger than or practically equivalent to that of the better-hearing ear (31).…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, 50% (1/2) of the patients with contralateral DEH showed the abnormal CP and vHIT in the previously deaf ear rather than the opposite ear. The pattern of ELH distribution and vestibular deficit is rather complicated in contralateral DEH, indicating that its pathology is more involved compared to its ipsilateral counterpart (30,32,33). Further studies with larger sample sizes are warranted to elucidate the pathogenesis.…”
Section: Discussionmentioning
confidence: 97%
“…During the past two decades, high-resolution MRI with gadolinium as the contrast agent has been shown to provide direct evidence of ELH in the inner ear in vivo, which facilitates diagnosis of hydropic ear disease (MD, DEH, etc.) [50][51][52]. Meanwhile, non-enhanced MRI can also differentiate the endo-and perilymph space and is of great clinical value in detecting ELH in MD patients [53], although this statement was under debate [54].…”
Section: Application Of Mri In Hydropic Ear Diseasementioning
confidence: 99%
“…Therefore, our data indicated that TSCP was less destructive theoretically by comparison with chemical labyrinthectomy. Iwasa et al 20 reported that in 19 cases of DEH, 6 patients were diagnosed with bilateral DEH (31.6%). So we should pay careful attention to this bilateral pathology and give priority to TSCP when compared with intratympanic gentamicin.…”
Section: Discussionmentioning
confidence: 99%